Epistemological criticism of the concept of individualism in conventional economies - Nalle, Frederic; Ismail, Munawar (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This research critically examines the epistemology surrounding the concept of individualism within conventional economics, focusing on elucidating the influence of non-economic factors—namely culture, social norms, and collective psychology—on economic decision-making processes. This study endeavors to uncover the role of these factors in individual economic decisions by employing a methodology rooted in analyzing economic and sociological literature. The findings shed light on the discordance between the traditional notion of individualism and the multifaceted realities of contemporary society, where culture, social norms, and collective psychology significantly shape economic behaviors and preferences. By providing nuanced insights into how these non-economic factors impact individuals' economic choices and actions, this research underscores the imperative for a broader, more inclusive perspective within economic paradigms. This study contributes to a richer comprehension of the complexities inherent in individual economic decisions when viewed against non-economic influences.